Comparison and Design of Multi-Storied Buildings in All Four Zones, By Using STAAD Pro - Pushkar Lal Sahu; Bhojram Sahu (International Journal of Scientific Research in Civil Engineering, 2025)
In civil engineering structure seismic design of multi-storey building requires both static and dynamic analysis are perform. Static analysis is performed for regular buildings upto 90m height in zone II & III. Dynamic analysis is performed for both regular and irregular buildings in zone IV & V. Dynamic analysis is eighter performed by the “Time History Method” or “Response Spectrum Method”. The weakness arises due to discontinuity in mass, stiffness and geometry of structure. Mass irregularity shall be considered to exist where the weight of any storey is more than 200% of that of its adjacent storeys. There is necessary to construct a structure which is earthquake resistance at a particular level of intensity of shaking a structure. The project consists of G+10 buildings with same plan. Irregular building (T-shape) is compared in all four zones. All these buildings are designed with same height and plan with their respective ideas. The designing has been carried out in STAAD.Pro software (software that deals with analysing and designing of structures. The modelling and graphics of this software is more clear and perfect and easy to understand). All the G+10 building structure and modelled, analysed and then designed for all four zones. Results are compared with respect to all zones. The base shear force, volume of concrete, weight of steel and cost effectiveness have been calculated to depict all the differences in structure behaviour when analysed in all four zones in STAAD.Pro software.
Keywords: staad pro; time history analysis